DEIKSIS DALAM NOVEL HATA BATAK SI TUMOING: PASIDING HOLANG PADIMPOS HOLONG KARYA SAUT POLTAK TAMBUNAN - Tio Bungani Artha Lestari Sihite; Charlina Charlina; Mangatur Sinaga (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is entitled Deixis in the Batak Hata Novel Si Tumoing: Pasiding Holang Padimpos Holong Works by Saut Poltak Tambunan. The background of this research is that the researcher wants to describe how the use of person deixis, place deixis, and time deixis. The purpose of this study is to describe the use of deixis persona, place deixis, and time deixis. This research is a qualitative descriptive study that describes the results of the research conducted. Based on the data collection techniques carried out in this study, there were 648 data. Through the data collection techniques carried out identified 533 person deixis, 70 datadeixis, and 45 data in the Deixis in the Batak Hata Novel Si Tumoing: Pasiding Holang Padimpos Holong Works by Saut Poltak Tambunan.Key Words: Deixis, the definition of deixis, a type of deixis.